Analisis Program Ta’limul Qur’an Di SMP Al-Azhar Menganti - Dinda Darma Wanti; Barudin (LPPM STAI Al-Azhar Menganti Gresik, 2022)
The Ta'limul Qur'an program is a derivative program of Pondok Pesantren, meaning that it sees the condition of the community's need for the desire of parents to house their children but the child does not feel at home and the parents are forced to finally take a middle way, namely the Ta'limul Qur' program. an. In general, this study aims to observe, describe and analyze: Planning. Implementation. And monitoring the evaluation of the Ta'limul Qur'an program at Al-Azhar Menganti Middle School. In this study using a qualitative approach. Data were collected through interviews, observation, and documentation, then the data were analyzed by contextual data covering three procedures in the study, namely: data reduction, data presentation, and drawing conclusions. The results of the analysis of the Ta'limul Qur'an program at SMP Al-Azhar Menganti include, Planning the Ta'limul Qur'an program at SMP Al-Azhar Menganti in general, from the side they learn, it is still general material and religious material, for fluency. learning begins with preparing lesson plans. The implementation of learning in the Ta'limul Qur'an program consists of 3 steps, namely: The initial activity contains greetings, asking news, praying, learning motivation, showing learning objectives. The core activity in the Ta'limul Qur'an program uses the MIDI module in the form of a summary of the material, full color. Using the sorogan and question and answer method. Closing activities contain closing statements, giving assignments, explaining the material to be discussed at the upcoming meeting and reading prayers. Monitoring the evaluation of the Ta'limul Qur'an program at SMP Al-Azhar Menganti for the Tahfidz program using an oral test and a written test. The oral test is in the form of memorizing and connecting verses, while the written test is writing what they have memorized. Those who manage to get 2 juz will be graduated. For Diniyah, they use an oral test, for those who have completed 6th tilawati are included in munaqosah which are tested directly by the munaqisy team from Al-Falah Surabaya and those who pass will be graduated. For monitoring the evaluation of learning activities there are weekly, monthly, incidental evaluations and evaluations from the curriculum leader.